Effect of different support materials in passive immobilization of clostridium saccharoperbutylacetonicum (n1-4) for biogas production - Muhammad Mustaqim Bin Rosli (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
This study was designed to focus some key environmental factors which were investigated for their effects on the yield and the rate of biogas production by Clostridium saccharoperbutylacetonicum N1-4. The rice husk and rice straw were physically pretreated using grinder before being sieved. Hemicellulose content in lignocellulosic was removed during steam explosion pretreatment (autohydrolysis). The initial glucose concentration of 10 g/L and initial pH of 6.0 0.2 at a temperature of 37C was the optimum condition for the bacteria to produce hydrogen. Furthermore, the addition of Fe2+ and sparging nitrogen were also identified as enhancing parameters towards optimum hydrogen yield and bacterial growth which improve in the previous study. Morphological of raw and solid pretreated rice husk and rice straw biomass had been observed by Scanning Electron Microscopy (SEM) and functional groups were determined by Fourier Transformed Infrared (FTIR) have shown significantly changed before and after pretreatment. Based on the result, the characterization analyses of the raw and pretreated sample illustrated significant physical changes of the both rice biomass after steam pretreatment. In order to maximise the production of biogas production, support material by rice biomass is used and based on dark fermentation, 3 runs with different types of support material condition were performed to identify the highest yield of biogas among the support materials. It was discovered that hydrogen production was increased from 334.6 ml for free cell and to 681 ml pretreated rice straw at 48 hours fermentation